1983
DOI: 10.1177/0093854883010004005
|View full text |Cite
|
Sign up to set email alerts
|

And Darkness Closes in...A National Study of Jail Suicides

Abstract: Inmates in county jails and police lockups commit suicide at a rate of 16 times greater than individuals in the general population. This conclusion was reached as a result of findings in a National Study of Jail Suicides. Documentation of 419 suicides in county and local jails during 1979 is presented. From demographic data collected on 344 of these suicides, a profile of the victim was constructed. The victim is most likely to be a 22-year-old, white, single male. He would have been arrested for public intoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
2

Year Published

1987
1987
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 1 publication
5
56
2
Order By: Relevance
“…Most studies (Topp, 1979;Burtch and Ericson, 1979;Hayes, 1983) have shown that the crude rate for suicide in prison is far in excess of that in the general population. In view of this and the fact that over 50 per cent of those prisoners committing suicide between 1958 and 1971 had a history of previous attempts (Topp, 1979) we are surprised that there have been so few studies of deliberate self-injury occurring in prison (Koller and Castanos, 1969;Rieger, 1971;Biegel and Russell, 1972;Cookson, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies (Topp, 1979;Burtch and Ericson, 1979;Hayes, 1983) have shown that the crude rate for suicide in prison is far in excess of that in the general population. In view of this and the fact that over 50 per cent of those prisoners committing suicide between 1958 and 1971 had a history of previous attempts (Topp, 1979) we are surprised that there have been so few studies of deliberate self-injury occurring in prison (Koller and Castanos, 1969;Rieger, 1971;Biegel and Russell, 1972;Cookson, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…First, MDOs are more likely than other inmates to engage in "disruptive" behavior potentially harmful to themselves, other inmates, or correctional staff (Adams, 1985;Toch & Adams, 1986;Uhlig, 1976). Second, incidents of suicide in correctional facilities raise concerns not only for suicide victims, but also for inmates and correctional staff traumatized by the experience (Hayes, 1983;Polvi, 1997). Third, empirical research shows that MDOs are much more likely to be victimized (i.e., physically and/or sexually assaulted) in prisons than non-mentally disordered offenders, or people in the community (Cooley, 1992).…”
Section: The Impact Of Mental Disorder In Prisons and Jailsmentioning
confidence: 99%
“…One reason for this is the contrast in the sheer numbers of jails compared to prisons (Hayes, 1983). Another reason is that prison inmates may have fewer support networks in the outside community than do jail inmates who are only recently removed from the community and possess closer contact with family and friends (Collins, 1995;Hayes, 1983). A problem in identifying case law specifically dealing with prison suicide arises from the defining standards themselves, in which the distinction between jail facilities and prison facilities is blurred, confused, or used interchangeably (Diaz-Ferrante v. Rendell, 1996;Jess v. Wagner, 1996).…”
Section: An Analysis Of Prison Suicide Liability Since Farmer V Brennanmentioning
confidence: 99%